Championing Green Marketing: Environmental Responsibility in Sapang Palay's Micro-Food Businesses - Santos, Jason C.; Sibayan, Loreta P.; Haber, Sarah Jane T. (International Journal of Applied Research in Management and Economics, 2024)
The study titled "Environmental Responsibility in Sapang Palay Market: A Look at Green Marketing in Local Micro-Food Businesses" delves into green practices and business operations. Through a quantitative analysis, the research reveals the utilization of environmentally conscious practices such as the use of energy-saving tools, waste segregation, and engagement in recycling through scrap reselling. Other eco-friendly practices such as the use of paper straws, while observed, turned out to be less prevalent. Notably, water and energy-conserving production practices and sustainable packaging emerged as significant drivers of sales, while effective waste management proves instrumental in fostering environmental growth. Although micro-food businesses demonstrate a notable utilization and integration of green practices, the findings suggest opportunities for improvement such as the prevalent use of plastic products, and Styrofoam which are scientifically proven to be detrimental to the environment as waste. Micro-Food Businesses continue to patronize these packaging options due to cost and profitability considerations. Collectively, the research underscores the critical need for heightened awareness and proactive measures to foster the widespread adoption of sustainable practices, advocating for the reduction of waste, energy conservation, and the use of non-toxic materials to promote a healthier and more environmentally conscious business landscape.